Local Culinary-Based Entrepreneurship Using the Canvas Business Model - Alip Suroto; Debby Fifiyanti (Akademi Kesejahteraan Sosial Ibu Kartini Semarang, 2024)
The restaurant business continues to grow, but few business actors understand how to seize business opportunities to increase competitiveness. This study aims to analyze the application of the Canvas Business Model (BMC) in the culinary industry, with a focus on the fast food business in the city of Surakarta. BMC is used to evaluate nine key elements: value proposition, customer segments, distribution channels, customer relationships, key resources, key activities, key partnerships, cost structure, and revenue streams. The method used in this study is a qualitative descriptive approach, with data collection through surveys, interviews, and observations. The results of the study show that the implementation of BMC can increase the effectiveness of business strategies, especially in terms of product innovation, improved customer experience, and optimization of digital marketing and partnership networks. In addition, a SWOT analysis is conducted to identify the strengths, weaknesses, opportunities, and threats of the culinary business, which is then used as a basis in designing a growth strategy. The main findings of this study propose new business models that are more adaptive and sustainable, including product diversification strategies, the use of digital technology, and strengthening partnerships with suppliers and food delivery service platforms. This research is expected to be a reference for culinary entrepreneurs in developing more competitive and sustainable business strategies in the digital era.